LIBER Endorses Action by Dutch Librarians - LIBER Quarterly (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
LIBER (Ligue des Bibliothèques Européenees de Recherche, the Association of European Research Libraries) endorses the opinion of UKB that the price increase of scholarly journals, notably those of some of the commercial publishers, has for years exceeded that which might be expected on the basis of price increases in general, currency rates and the expansion of the market. LIBER agrees with the opinion of the UKB that - where there used to be a certain balance between the various parties in the information chain - this balance has been irresponsibly disturbed by the price policies of a number of publishers. This is detrimental to the services of libraries to their users, and hence to the development of science.